2019
DOI: 10.1088/1742-6596/1402/2/022037
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain support factors for brown sugar business optimality using analytical hierarchy process

Abstract: The sustainability of business activity is determined by the existence of all elements involved in business activity. Alignment of each component included in business activities can be determined by identifying supporting factors based on movements in each business chain that occurs. This study aims to determine the supporting factors for the optimality of supply chain performance of brown sugar business activities using the supply chain management approach and supported by the analytical hierarchy process met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Kunz and Crones (2015) in analyzing the monetary implications in constraining price vectors which maximize the different single objectives, identified (i) profit, (ii) revenue, and (iii) unit sales, as well as (iv) balanced multiple objective solution as the efficiency measures of a retail revenue management system. Likewise, Ikhwana et al (2019) suggested that business optimization involves cooperation ranging from the supply of raw materials, processing raw materials, manufacturing, to consumers, in an activity integrated manner. As such, Ikhwana et al (2019) defined operational efficiency along quality of materials, price of materials and timeliness of delivery of a firm's product or service.…”
Section: Operational Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Kunz and Crones (2015) in analyzing the monetary implications in constraining price vectors which maximize the different single objectives, identified (i) profit, (ii) revenue, and (iii) unit sales, as well as (iv) balanced multiple objective solution as the efficiency measures of a retail revenue management system. Likewise, Ikhwana et al (2019) suggested that business optimization involves cooperation ranging from the supply of raw materials, processing raw materials, manufacturing, to consumers, in an activity integrated manner. As such, Ikhwana et al (2019) defined operational efficiency along quality of materials, price of materials and timeliness of delivery of a firm's product or service.…”
Section: Operational Efficiencymentioning
confidence: 99%
“…Likewise, Ikhwana et al (2019) suggested that business optimization involves cooperation ranging from the supply of raw materials, processing raw materials, manufacturing, to consumers, in an activity integrated manner. As such, Ikhwana et al (2019) defined operational efficiency along quality of materials, price of materials and timeliness of delivery of a firm's product or service. Essuman et al (2020) added that operational efficiency reflects how well a firm minimizes "costs" (such as, actual monetary expenses either direct and or indirect paid incurred and volume of wastes in operations like waste of material and idle capacity) associated with administering its business operations.…”
Section: Operational Efficiencymentioning
confidence: 99%
“…Palm sugar business is a business that involves various parties, including farmers as a producers and raw material supply who play a role in providing assurance regarding the availability of raw materials which are distributed to collectors or selling directly to processing raw materials for brown sugar [8]. Business optimization that involves cooperation ranging from raw material supply, raw material processing, manufacturing and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…State Of The Art dalam penelitian ini mengutip dari hasil penelitian Dosen Teknik Industri Institut Teknologi Garut yaitu [3] Hubungan antar elemen rantai pasok pada komoditas kopi dapat mendukung dalam mendistribusikan produk, dan digunakan sebagai media umpan baik jika ada perubahan standar kualitas yang diperlukan sesuai dengan kebutuhan konsumen serta komitmen bersama antar setiap elemen rantai pasokan diperlukan terutama dalam menentukan kualitas dan kuantitas produk. [17] Dampak terbesar dari seluruh elemen dalam rantai pasokan yaitu reliability atau keandalan bisnis adalah hal yang perlu diperhatikan dalam elemen rantai pasokan untuk menghasilkan jalan potensial untuk penelitian ke depannya terutama bagi para pebisnis baru. [5] Keberlanjutan usaha ditentukan oleh keberadaan seluruh elemen yang terlibat dalam aktivitas bisnis, kualitas produk, biaya pembelian gula merah, bahan baku, dan ketetapan serta kesesuaian jumlah pengiriman yang sesuai permintaan adalah unsur yang dapat mendorong keberlanjutan usaha gula merah.…”
unclassified